THE ESSENCE AND FUNDAMENTAL PRINCIPLES OF THE EFFICIENCY OF ENTREPRENEURIAL ENTITIES (Development Service Industry Management, 2024)
The article is devoted to the study of the essence and basic principles of efficiency of functioning of entrepreneurial entities (EEs) in the context of dynamic development of market relations and globalization processes. It is determined that the effective operation of EEs is a key factor in economic growth, job creation and improvement of living standards. The main problems that complicate ensuring high efficiency of entrepreneurship, such as instability of the economic environment, high level of competition, insufficient level of financial resources, low adaptability to technological changes, and problems with management and organization are analyzed. The dynamics of changes in the number of EEs in Ukraine for 2016-2023 is presented, in particular, the growth trends of large EEs, the stability of medium-sized ones and significant fluctuations in small joint ventures, which indicates the impact of military operations and economic changes. The authors prove that the economic efficiency of EEs can be generally characterized as the ratio of results to costs. The article provides indicators of performance of a EEs, which can be both absolute and relative. The main absolute indicator is profit. The factors influencing the efficiency of business entities are formed, based on the classification of these factors it is possible to model the activities of EEs  and search for internal reserves to improve efficiency. It is proved that the proposed factors are interconnected and influence each other, so it is important to consider them in a complex to achieve maximum efficiency. It is also determined that in order to improve the efficiency of EEs, it is necessary to apply an integrated approach and analytical methods, such as SWOT analysis, PEST analysis, financial ratios and efficiency assessment models. This approach to improving the efficiency of business entities using various analytical methods is key to their successful development.
Keywords: entrepreneurial entities; entrepreneurship; entrepreneurial activity; principles of formation; factors of influence